Sustainable Energy, the Climate Industrial Complex, and Windmills - Manheimer, Wallace (European Journal of Applied Sciences, 2023)
This article makes the case that 1: A reasonable approach to economically and environmentally viable sustainable energy, an approach that is able to sustain modern civilization now and in the future, is a continued use of fossil fuel, followed by a gradual change to nuclear power first fueled by mined uranium, and then later on by breeding nuclear fuel; 2: While the climate always has changed and always will, there is no climate crisis; and 3: Windmills, solar panels and batteries alone are not viable power sources for a modern civilization. They are neither economically, nor environmentally viable.